Design and Validation of an Antipodal Vivaldi Antenna with Additional Slots - Marek Dvorsky; Harihara S. Ganesh; S. Sadhish Prabhu (International Journal of Antennas and Propagation)
This paper introduces an improved shape of Antipodal Vivaldi Antenna from the normal schematic structure which yields a high radiation gain. We have designed and fabricated the improved structure of Antipodal Vivaldi Antenna with the help of new dielectric substrate ASTRA®MT77 material. We have chosen a unique substrate material to develop our novel Antipodal Vivaldi Antenna because most research has been done on commonly used materials like FR4, RT Duroid, etc. Moreover, ISOLA has significantly good electrical and nonelectrical properties as compared with other substrate materials. The results of the desired antenna were simulated through extensive simulations performed in CST Microwave Studio®. The characteristics of all the antenna parameters are clearly studied and we are successful to achieve closed results between designed as well as experimented Vivaldi Antenna. The simulated antenna achieved a maximum gain of more than 9 dBi whereas the experimental antenna reached around 7 dBi between the operating frequency range from 1 GHz to 13 GHz. The measured prototype antenna provides linear polarization with overall radiation efficiency of more than 90%.